Segurança jurídica, princípio da legalidade tributária e jurisprudência - Santos, Bianca Mizuki Dias dos (2009)
The subject matter of this work is the analysis of the concept of legal security in the Brazilian Federal Constitution of 1988, especially with regard to the activity of taxation by the state. Legal security is not isolated in the normative context, because there are other values related to legal security, such as justice and equality. Although they are different values, there is no antinomy or conflict between them, because they are considered to be fundamental values of the Brazilian Democratic State that abides by the Rule of Law. As a value, legal security needs to gain objectivity, that is, there must be a support to hold this value, because values only exist with reference to a support and to man (the value is nonexistent per se). In this regard, the support chosen to fulfill legal security in the context of taxation is the principle of tax legality. This principle is the best underpinning of legal security in the Brazilian legal system, because it guarantees that individual freedom to own property may only be limited by law. Pragmatically, some significant cases will be analyzed in order to verify if the Brazilian Supreme Court acknowledge the relevant function of the principle of tax legality to achieve Legal security